Building an Environmental Culture: The Role of Leaders in Encouraging Ecological Awareness in Islamic Education Institutions - Abdullah, Asep; Indriana, Nina; Syah, Muhibbin; Nursobah, Asep; Ridwan, Mohammad; Hisniati, Sally Badriya (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
Islamic education plays an important role in forming ecological awareness among its followers. This research aims to explore the role of leaders in strengthening environmental awareness in Islamic educational institutions, by highlighting the approach methods used. Through qualitative analysis based on a literature study of relevant literature, this research reveals the importance of the role of leaders in promoting ecological awareness through a structured approach in Islamic educational institutions. Leaders can integrate environmental values into the curriculum, organize educational programs, and be role models for students. These findings provide a deeper understanding of leaders' strategies in strengthening ecological awareness, so that they can make a more significant contribution to environmental conservation.